Differences of use between paliperidone palmitate 3 month and paliperidone palmitate 1 month in real practice, with psychotic patients - P. Escobedo-Aedo; J. Merayo-Cano; L. Mata Iturralde; L. Muñoz Lorenzo; S. Ovejero; S. Sánchez Alonso (European Psychiatry, 2022)
Introduction Paliperidone palmitate 1-month (PP1M) is a Long-acting injectable antipsychotic formulation, approved for the treatment of schizophrenia and schizoaffective disorder. Recently, paliperidone palmitate 3-months (PP3M) formulation was introduced, which maintains stability while offering a longer dosing interval for the maintenance treatment in patients previously treated with PP1M. Despite of this, many patients are treated with PP1M without transition to PP3M.